Shenmai injection in treating chemotherapy-related cardiotoxicity of breast cancer: a systematic review and meta-analysis - Ming Feng; Hong Huang; Chang Yao (2024)
Abstract Shenmai injection (SMI) is an established treatment for cardiac diseases, and we performed to evaluate the efficacy of SMI combined with chemotherapy drugs for the treatment of chemotherapy-induced cardiotoxicity. The primary outcome was abnormal ECG, LVEF and E/A. The secondary outcomes included myocardial injury biomarkers (CK, CK-MB, and cTnI) and lipid peroxide markers (SOD, GSH, and MAD). Studies indicated that SMI combined with chemotherapy drugs has advantages over chemotherapy drugs alone in reducing the incidence of abnormal ECG (ST-T: RR = 0.613, 95% CI [0.437, 0.862], p = 0.005; extrasystole: RR = 0.527, 95% CI [0.349, 0.798], p = 0.002). Myocardial injury biomarkers in the experimental group were lower than those in the control group (CK: SMD = − 2.614, 95% CI [–3.156, − 2.071], p = 0.000; CK-MB: SMD = − 6.882, 95% CI [–8.982, − 4.782], p = 0.000; cTnI: SMD = − 3.610, 95% CI [–4.949, − 2.271], p = 0.000). Ultrasonic cardiogram analysis showed that the experimental group had a higher LVEF and E/A than the control group (LVEF: SMD = 1.572, 95% CI [1.176, 1.969], p = 0.000; E/A: SMD = 0.280, 95% CI [0.153, 0.407], p = 0.000). Lipid peroxide meta-analysis showed that the experimental group had higher SOD and GSH levels (SOD: WMD = 39.783, 95% CI (32.524, 47.042), p = 0.000; GSH: WMD = 32.960, 95% CI [26.055, 39.865], p = 0.000), and lower MDA (WMD = − 4.962, 95% CI [–6.041, − 3.883], p = 0.000). SMI is effective in reducing cardiac injury and the incidence of cardiotoxicity.